Gross motor skill performance in children with and without CHARGE syndrome: Research to practice. (August 2019) - Haibach-Beach, Pamela; Perreault, Melanie; Foster, Elizabeth; Lieberman, Lauren
Highlights: We examined motor skills in children with and without CHARGE syndrome. Children with CHARGE syndrome performed significantly behind their typically developing peers in all motor skills assessed. The locomotor skill most significantly delayed was the run and the object control skill most significantly delayed was the throw. Large negative associations were found between age of walking and most motor skills assessed in children with CHARGE. Abstract: Background: CHARGE syndrome is a multifaceted syndrome of complex birth defects. The heterogeneous nature of children with CHARGE syndrome brings unique issues and challenges affecting the overall motor development of the child, often resulting in developmental delays including motor delays. Aims: The purpose of this research was to assess children with CHARGE Syndrome on locomotor and object control skills to better understand their motor development. This information is relevant to adapted physical education teachers, paraeducators, vision teachers, health care professionals (occupational therapists, physical therapists, and physicians) and parents and family members of children with CHARGE Syndrome. Methods and Procedures: Thirty-seven children with CHARGE syndrome and thirty peers without disabilities participated in the study. Each participant was assessed on two object control and three locomotor skills with modifications, if necessary. In addition, the age of onset of independent walking was recorded for each participant. Outcome and results: Children with CHARGE syndrome performed significantly behind their same age peers in most gross motor skills with the biggest deficits found in the run and kick. Age of onset of walking was associated with performance in jumping, running, and throwing. Conclusions and implications: Early intervention services should focus on gross motor skills such as throwing, kicking, as well as walking at an early age.